The complete stories - Malamud, Bernard 1914-1986 (Farrar, Straus and Giroux, 1997)
More than 50 stories on the Jewish experience this century. They chronicle the lives of Old Country ancestors, refugees, immigrants or just simple wanderers like the anti- hero Fidelman. The settings are on both sides of the Atlantic.
Keywords: Juden; Jews -- Fiction; Short stories